PERENCANAAN STRUKTUR GEDUNG @HOM HOTEL KUDUS BERDASARKAN SNI 03-1726-2012 - Wibowo Budi; Januar Reza; Sri Tudjono; Parang Sabdono (Jurnal Karya Teknik Sipil, 2015)
The structure of @HOM Hotel Kudus building design by SNI 03-1726-2012. To obtain ductile structure, special moment resisting frame (SRPMK) used. The analysis of the structure using SAP2000 software. Loading structure refers to SNI 03-1727-2013. Required for earthquake resistant buildings should not happen bristle failure. Thus the plastic hinge detail and beam-column joint must be calculated correctly. Lateral deflection requirements beetween floors should be controlled so that the stiffness of structure is not soft.